P92 Effectiveness and safety of mepolizumab in real-world clinical practice: UK patient outcomes from the REALITI-A study. (12th November 2019) - Kerr, WAF; Harrison, TW; Loveday, K; Joksaite, S; Kwon, N
Abstract : Introduction and objectives: REALITI-A is a prospective, open label, observational cohort study designed to collect observational data in real-world settings from severe eosinophilic asthma (SEA) patients treated with mepolizumab. The study aims to describe the effectiveness and safety of mepolizumab in real-world clinical practice. In this interim analysis, we describe the 12-month outcomes from the United Kingdom (UK) patients enrolled in the study. Methods: REALITI-A is a 2 y, global, prospective, single-arm, observational cohort study enrolling pts with SEA and newly prescribed mepolizumab 100 mg SC at physician's discretion. Data were collected at routine healthcare visits; 1 y pre-exposure data were collected retrospectively at enrolment. Primary endpoint was rate of clinically significant exacerbations (CSEs; requiring OCS and/or emergency room [ER] visit/hospitalisation). Exacerbations requiring ER visit/hospitalisation and maintenance OCS (mOCS) use were key secondary endpoints; treatment-related AEs were reported. This interim analysis includes 136 pts enrolled in the UK with 1y post-exposure data. Results: 136 treated pts from a total of 368 were enrolled in the UK and included in this analysis (mean age, 51y; 65% female; geometric mean blood eosinophil count, 265 cells/µL; smoker: former 34%/current 2%, never 64%; 69% current mOCS). The rate ratio (RR) of CSEs was 0.41 (95%CI 0.36, 0.47; 6.19 [pre-] reduced to 2.54 [post exposure] events/y); RR of exacerbations requiring hospitalisation/ER visits was 0.26 (0.19, 0.35; 1.65 reduced to 0.42 events/y). mOCS data were available for 89 (baseline) and 77 (Wk 53–56) pts. Median mOCS dose reduced from 10 to 5 mg/day at Wk 53–56; 26% (20/77) stopped OCS. 35 (26%) pts had on-treatment AEs and 2 (1%) had serious AEs; there were no fatal AEs. Conclusions: Significant reductions in exacerbations and OCS use with mepolizumab in clinical trials translate to a UK real-world setting. This provides assurances of the effectiveness and safety of mepolizumab in a discrete population with a high burden of disease.